Perancangan User Experience Aplikasi Pencarian dan Manajemen Indekos berbasis Android dengan pendekatan Human-Centered Design - Amir Saqib Azhardika; Herman Tolle; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The rapid development of information technology and the internet leads to the emergence of applications that aim to facilitate people's work to daily basis. Almost all areas in daily life have been helped by the available applications, varied in buying and selling activities, education, banking, to flat seeking. Therefore, there are still problems in the concerning seeking and managing flats. Flat tenants deal the difficulty of the limited options for conventional searching, manual way of getting around to get information, and problem when do the searching through social media because of the lack of optimal searching features such as filters and homogenous of information. The flats owners also deal with the difficulty due to the limited advertising and flats management such as personal data recording, rental time reminders, and billing notifications. In addition to features, it also requires an easy-to-use and fast interface to learn so that users want to use the application for a long period. Therefore, it is necessary to design the user experience of mobile application for searching and managing flats. This design applies the HCD approach, because it is considered best in knowing the needs of users properly. After completing the design process, this design involves a usability evaluation with scenario task method and SUS questionnaire in 6 respondents for each type of user. From the evaluation of tenant users and owners, it obtains the effectiveness values of 90.5% and 95.8%, efficiency values of 91.4%, and 93.3%, and satisfaction values of 80.4 and 80.